THE INFLUENCE OF USING NURSERY SONG IN LEARNING VOCABULARY AT SMP NEGERI 3 KABUPATEN SORONG - Agustina Panca Astuti Klau; Rizqi Claudia Wardani H; Agus Setiawan (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The objective of this research is to find out whether or nor the use of Nursery Song influence in learning vocabulary at seventh gradde of SMP Negeri 3 Kabupeten Sorong. Related to this research used a pre-experimental quantitati research design. The research design is one group pretest-posttest. The sample of this research was seventh grade students and the total are 20 students. In the collecting data, the researcher used a vocabulary test in the form of multiple- choose that is consist of 20 questions for the pretest and posttest. In analyzing the data, the researcher used the SPSS 20 program to calculate research the data. The result finding of the reseach showed that the result of the t-test is P value (0.00) < (0.05). it means that H0 was rejected and Ha was accepted. The alternative hypothesis (Ha) was there is an influence in learning vocabulary using nursery song between pretest and pos ttest. In addition, it can be seen from the pretest was (63,5) improved on posttest (98,0). It can be concluden that there is an influence in learning vocabulary using nursery song.